Acute HIV infection presenting as fulminant meningoencephalitis with massive CSF viral replication - Andrade, Rosa M. (Lippincott Williams & Wilkins, 2014)
A 22-year-old man presented to the emergency department with 10 days of malaise, generalized rash, sore throat, oral ulcers, headache, nausea, and vomiting. On examination he had fever (101.5°F), hepatosplenomegaly, generalized maculopapular rash, and lymphadenopathy. He rapidly became obtunded, requiring intubation. Initial laboratory studies showed mild transaminitis, increased lactate dehydrogenase, and 4,600 leukocytes per μL with 61% bands and 18% lymphocytes. Bacterial and fungal blood cultures were negative as well as a rapid HIV test, additional serologies (including rapid plasma reagin and Treponema pallidum particle agglutination), quantitative PCRs (for viruses other than HIV), and urine and blood toxicology. CSF, on hospital day 4, showed a lymphocytic pleocytosis (total leukocytes: 100), high protein, borderline hypoglycorrhachia, and negative Gram stain and culture. Brain MRI revealed no meningeal enhancement or masses. EEG revealed no epileptiform activity. Flow cytometry on bone marrow biopsy and CSF found no evidence of malignancy; neither did an excisional lymph node biopsy (figure 1). An immunofluorescent assay test for HIV returned inconclusive and a Western blot detected HIV gp120/gp160 bands. Quantitative HIV RNA PCR was 1.4 × 10(6) copies/mL in plasma and in CSF exceeded the upper limit of quantitation (10(7) copies/mL) (figure 2).